SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA GURU SMA NEGERI 1 ROWOSARI KENDAL (Information Technology and Telematics, 2013)
Decision Support System is a set of model-based procedure for data processing and assessment to assist managers in making decisions. In this research, Decision Support Systems implemented in SMA Negeri 1 Rowosari Kendal useful to assist the Principal in the performance appraisal of teachers. During this time the teacher performance evaluation system conducted in SMA Negeri 1 Rowosari Kendal still using manual systems so that the result in decisions that require a relatively need a long time.  Based that, it was made in the computerized system of decision-making teacher performance assessment, in order to produce a fast and accurate decisions . With the use of decision support systems application performance appraisal of teachers using Analytical Hierarchy Process (AHP), the mistakes made when making decisions such as the delay in taking a decision can be reduced because the computerized system.Keyword Analytical Hierarchy Process (AHP), Decision Support System Teacher Performance.